Local and systemic inflammation triggers different outcomes of tumor growth related to infiltration of anti-tumor or pro-tumor macrophages. Issue 15 (5th August 2022) - Liu, Xinghan; Jiang, Qi; Shen, Sunan; Hou, Yayi
Abstract: Background: Previous evidence suggests inflammation may be a double-edged sword with cancer-promoting and cancer suppressing function. In this study, we explore the impact of local and systemic inflammation on cancer growth. Methods: Female BALB/C mice were subcutaneously implanted with foreign body (plastic plates) to build up a local inflammation and intraperitoneally injected with PolyIC or lipopolysaccharides (LPS) to build up a systemic inflammation, followed by subcutaneous injection of 5  × 10 5 colon cancer cells. Immunohistochemistry and enzyme linked immunosorbent assay were utilized to detect the Ki67 and interleukin (IL) 6, IL-1β, and monocyte chemoattractant protein-1 expression in the tumor tissues and serum, respectively. The distributions of immune cells and expression of toll-like receptors (TLRs) were evaluated by flow cytometry (FCM) and quantitative real time-polymerase chain reaction. Results: The results showed that local inflammation induced by foreign body implantation suppressed tumor growth with decreased tumor weight ( P   =  0.001), volume ( P   =  0.004) and Ki67 index ( P   <  0.001). Compared with the control group, myeloid-derived suppressive cells sharply decreased ( P   =  0.040), while CD4 + T cells slightly increased in the tumor tissues of the group of foreign body-induced local inflammation ( P   =  0.035). Moreover, the number of M1 macrophages ( P   =  0.040) and expression of TLRs, especially TLR3 ( P  < 0.001) and TLR4 ( P  < 0.001), were significantly up-regulated in the foreign body group. Contrarily, tumor growth was significantly promoted in LPS or PolyIC-induced systemic inflammation ( P   =  0.009 and 0.006). FCM results showed M1 type macrophages ( P   =  0.017 and 0.006) and CD8 + T cells ( P   =  0.031 and 0.023) were decreased, while M2 type macrophages ( P  = 0.002 and 0.007) were significantly increased in tumor microenvironment of LPS or PolyIC-induced systemic inflammation group. In addition, the decreased expression of TLRs was detected in LPS or PolyIC group. Conclusions: The foreign body-induced local inflammation inhibited tumor growth, while LPS or PolyIC- induced systemic inflammation promoted tumor growth. The results suggested that the different outcomes of tumor growth might be attributed to the infiltration of anti-tumor or pro-tumor immune cells, especially M1 or M2 type macrophages into tumor microenvironment.